Applying Augmented Reality in Color and Aesthetic Education: An Empirical Study on Enhancing Learning Outcomes of Students in a Five-Year Junior College Beauty Program - YEH, JU-HSUAN (Universitas Negeri Semarang, 2025)
This study aimed to investigate the impact of integrating Augmented Reality (AR) technology into color and aesthetics education on the learning effectiveness of students enrolled in a five-year junior college beauty program. The research was conducted at a vocational college in northern Taiwan, targeting 58 first-year female students (aged 16–17) from the Department of Cosmetic Application and Management. All participants were enrolled in a required color and aesthetics course and had no prior experience using AR technology in educational settings, allowing for an objective assessment of AR as a novel instructional tool. A mixed-methods approach was adopted, combining paired-samples t-tests to analyze pre- and post-test data with qualitative methods such as student interviews and project work analysis. The results demonstrated that AR-created immersive and multisensory learning environments enabled students to visualize and simulate color combinations under varying lighting and material conditions, deepening their understanding of color theory and coordination. Moreover, the interactive features of AR fostered real-time collaboration and stimulated creative thinking and problem-solving. Compared to traditional teaching methods, AR-integrated instruction significantly enhanced students' motivation, professional skill development, and overall satisfaction. These findings confirm the feasibility and pedagogical value of using AR in beauty education, offering both theoretical insights and practical evidence for its implementation in vocational and interdisciplinary curricula.